Physico-chemical and biological study of excision-repair of UV--irradiated phiX174 RF DNA in vitro. - Heijneker, H L (1975)
We have studied excision-repair of UV-irradiated phiX174 RFI DNA in vitro with UV-specific endonuclease from Micrococcus luteus (UV-endo), DNA polymerase I from Escherichia coli and DNA ligase from phage T4 infected E. coli. Excision-repair was measured a) by physico-chemical methods, i.e. by determination of the conversion of RF I DNA into RF II DNA by UV-endo and by the subsequent conversion of RF II DNA ligase, b) by biological methods i. e. by measuring the ability of the reaction product to form phages upon incubation with spheroplasts from the appropriate strains of E. coli. Using the first method, we have shown, that more than 90% of the pyrimidine dimers can be repaired in vitro; with the latter method we have shown, that the molecules which are repaired as defined by method a) have regained full biological activity. Exonuclease III was found to be not essential for excision-repair in vitro and also did not stimulate repair. From this result we conclude that UV-endo generates 3'OH endgroups, in agreement with results obtained by Hamilton et al. (1974). The usefulness of the method presented in this paper with regard to the study of excision-repair is discussed.